2021
DOI: 10.1530/joe-20-0446
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is associated with heavy menstruation that may be due to delayed endometrial repair

Abstract: Heavy menstrual bleeding is common and debilitating but the causes remain ill defined. Rates of obesity in women are increasing and its impact on menstrual blood loss (MBL) is unknown. Therefore, we quantified BMI and MBL in women not taking hormones and with regular menstrual cycles and revealed a positive correlation. In a mouse model of simulated menstruation, diet-induced obesity also resulted in delayed endometrial repair, a surrogate marker for MBL. BrdU staining of mouse uterine tissue revealed decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
1
14
0
2
Order By: Relevance
“…The study was based on cross-sectional data and consequently, causal conclusions could not be drawn. Furthermore, we cannot exclude, that differential indications for the gynecological surgeries could be related to metabolic phenotype and thereby confound the results as both uterine fibroids and heavy menstrual bleedings are more frequent with obesity 53 , 54 . However, types of surgeries were evenly distributed between pre- and postmenopausal women suggesting that the confounding effect was limited.…”
Section: Discussionmentioning
confidence: 97%
“…The study was based on cross-sectional data and consequently, causal conclusions could not be drawn. Furthermore, we cannot exclude, that differential indications for the gynecological surgeries could be related to metabolic phenotype and thereby confound the results as both uterine fibroids and heavy menstrual bleedings are more frequent with obesity 53 , 54 . However, types of surgeries were evenly distributed between pre- and postmenopausal women suggesting that the confounding effect was limited.…”
Section: Discussionmentioning
confidence: 97%
“…4 C, D, 5 B). Of the hypoxia signaling, known HIFα-regulated genes include ADM [ 28 ], VEGFA [ 12 , 29 ], PDK3 [ 30 ], LOX [ 31 ], MXI1 [ 32 ], PDK1 [ 33 ], XPNPEP1 [ 34 ], SLC2A1 [ 34 ], IRS2 [ 35 ], and PFKFB3 [ 36 ], which have been shown to promote tumor growth and progression in various types of cancers. Previous reports showed that tumorigenesis is promoted via upregulation of glycolysis by ENO2 [ 37 ], PGK1 [ 38 ], ERO1A [ 39 ], P4HA1 [ 40 ], and IRS2 [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Yunhui Tang, the odds of having heavy menstrual bleeding were less in underweight individuals as compared to those with normal BMI [ 30 ]. Increased menstrual blood loss in obese women is attributed to delayed endometrial repair secondary to a proinflammatory local endometrial environment in obese women [ 31 ]. Likewise, delayed endometrial repair in underweight females could be liked with the role of nutrition in healing.…”
Section: Discussionmentioning
confidence: 99%